Kecacingan yang ditularkan melalui tanah pada anak sekolah dasar di Desa Picuan Baru Kecamatan Motoling Kabupaten Minahasa Selatan - Seroan, Alfa Yoan; Pijoh, Victor D.; Tuda, Josef S. B. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2018)
Background: Intestinal helminthiasis which transmits through soil is an infectious disease which is still a health problem in Indonesia. This disease can be found in most parts in Indonesia and can bring disadvantages with long-term impacts. This disease receives less attention than it should, even though it mostly affects children in the age range of elementary school. Aim: This study was conducted with the aim to depict the intestinal helminthiasis in elementary school children in Picuan Baru Village, Motoling Sub-district, South Minahasa District. Method: The study design used was descriptive survey study. The study subjects were children from grade I to VI at GMIM Elementary School and Inpres Elementary School of Picuan Baru Village. Result: Sampling is in the form of feces as many as 66 samples were collected and the results of examination showed negative results in the whole sample.Conclusion: The result of the study conducted about intestinal helminth infection on elementary school children at Picuan Baru Village, Motoling Sub-district, South Minahasa District showed negative results in the whole sample.